Effects of complex-contrast training on physical fitness in male field hockey athletes - Thapa Rohit K.; Kumar Gopal; Weldon Anthony; Moran Jason; Chaabene Helmi; Ramirez-Campillo Rodrigo (Sciendo, 2023)
Study aim: This study aimed to examine the effects of a six-week complex-contrast training (CCT) intervention on the physical fitness of male field hockey athletes.